Navigating the Transition to Energy Efficient Shipping: Main Currents and Critical Issues - A Review of Recent Research - Rodin, Simeon (My University, 2017)
Context: There is increasing awareness and concern over climate change and the shipping industry is under pressure to reduce emissions and transition towards green shipping practices. Energy efficiency is likely to play a gradually more important part in the shipping industry's climate change mitigation efforts. Objective: To conduct a literature review of current published research on energy efficiency measures and practices within the maritime shipping industry. To summarize the knowledge, identify potential challenges and contribute towards a broad understanding of the subject. Methods: Integrative literature review incorporating key elements of the systematic review process. Database searches were performed using Web of Science, Scopus, and Science Direct, and were limited to peer-reviewed articles published between 1 January 2012 and 19 April 2017. Results: Preliminary searches returned a total of 889 results. Search filters and limitations were applied and duplicates removed. The abstracts of 312 unique articles were screened. 107 full-text articles were retrieved and read to determine eligibility. 17 articles met all the criteria and are included in this review. Conclusion: There are still numerous challenges to overcome, but there has also been considerable progress made in the relevant fields toward increasing understanding of these challenges and the knowledge base is growing. In addition, companies and professionals in the shipping industry are becoming increasingly aware of these issues and are accumulating direct experience in this regard. For these reasons, they will likely be an important source of change and innovation.
Keywords: Farkostteknik; Hållbar utveckling; Transport; Vehicle Engineering; Sustainable Development; Transport